2020
DOI: 10.1001/jamaoncol.2020.0249
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Delayed Targeted Intraoperative Radiotherapy vs Whole-Breast Radiotherapy on Local Recurrence and Survival

Abstract: IMPORTANCE Conventional adjuvant radiotherapy for breast cancer given daily for several weeks is onerous and expensive. Some patients may be obliged to choose a mastectomy instead, and some may forgo radiotherapy altogether. We proposed a clinical trial to test whether radiotherapy could be safely limited to the tumor bed. OBJECTIVE To determine whether delayed second-procedure targeted intraoperative radiotherapy (TARGIT-IORT) is noninferior to whole-breast external beam radiotherapy (EBRT) in terms of local … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
74
2
4

Year Published

2020
2020
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(83 citation statements)
references
References 38 publications
3
74
2
4
Order By: Relevance
“…Based on our institutional guidelines which was prepared with a joint committee of experts in surgical oncology, radiation oncology and considering the guidelines of the American Society for Radiation Oncology, and the American Society of Breast Surgery, ELIOT and TARGIT trials (5,(9)(10)(11), patients with the following criteria received IORT as part of their treatment regimen: 1) Age equal or older than 45 years old; 2) Regarding histology all cases of invasive carcinomas were considered candidates, moreover in lobular carcinomas caution was taken and these patients were considered candidates only after MRI and con rmation of the radio-oncologist, and in cases with ductal carcinoma in-situ (DCIS) only those with low, intermediate grade, tumor size of equal or less than 2.5 cm and a margin of 2-3 mm were considered candidates; 3) Regarding tumor size those between 45 and 50 years old with a tumor size of 0-2 cm, those between 50 and 55 years old with a tumor size of 2-2.5 cm, and those equal and more than 55 years old with a tumor size of 2.5-3 cm were considered candidates; 4) Regarding marginal status those with invasive tumors a negative margin is considered su cient and in cases of DCIS a margin of 3 mm was considered a candidate; 5) Regarding nodal status patient should have a negative nodal status and the exception is considered in patients with micrometastasis; 6) Regarding hormone receptor status, patients should have a positive estrogen receptor status.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our institutional guidelines which was prepared with a joint committee of experts in surgical oncology, radiation oncology and considering the guidelines of the American Society for Radiation Oncology, and the American Society of Breast Surgery, ELIOT and TARGIT trials (5,(9)(10)(11), patients with the following criteria received IORT as part of their treatment regimen: 1) Age equal or older than 45 years old; 2) Regarding histology all cases of invasive carcinomas were considered candidates, moreover in lobular carcinomas caution was taken and these patients were considered candidates only after MRI and con rmation of the radio-oncologist, and in cases with ductal carcinoma in-situ (DCIS) only those with low, intermediate grade, tumor size of equal or less than 2.5 cm and a margin of 2-3 mm were considered candidates; 3) Regarding tumor size those between 45 and 50 years old with a tumor size of 0-2 cm, those between 50 and 55 years old with a tumor size of 2-2.5 cm, and those equal and more than 55 years old with a tumor size of 2.5-3 cm were considered candidates; 4) Regarding marginal status those with invasive tumors a negative margin is considered su cient and in cases of DCIS a margin of 3 mm was considered a candidate; 5) Regarding nodal status patient should have a negative nodal status and the exception is considered in patients with micrometastasis; 6) Regarding hormone receptor status, patients should have a positive estrogen receptor status.…”
Section: Patientsmentioning
confidence: 99%
“…Although our experience showed good outcomes at 24 months (median) follow-up, long term follow-ups are still lacking due to the novelty of the procedure in our region and institution. In this study we merely reported on clinical outcomes and epidemiology of patients who received IORT in our institution, it would be interesting to cross compare these patients with those who had similar BC conditions and received WBR to evaluate percentage of local recurrence as some studies have shown that these individuals will experience higher rates of local recurrence (11).…”
Section: Criteriamentioning
confidence: 99%
“…With further follow-up, the post-pathology cohort (1153 patients) was found to have increased LR with IORT at 5 years (3.96% IORT vs. 1.05% WBI), exceeding the noninferiority threshold and supporting the conclusion that this approach should not be offered to patients at this time. 4 With respect to the pre-pathology group, LR was elevated with IORT at 5 years (2.11% IORT vs. 0.95% WBI), though within the non-inferiority criteria; long-term Kaplan-Meier curves for LR were not presented by the investigators. 5 However, significant concerns have been raised regarding the methodology of these updates; the study did not present long-term absolute LR rates but rather local recurrence-free survival (LRFS).…”
mentioning
confidence: 92%
“…The trial was designed as a noninferiority trial, and failed to show noninferiority. 6 To be included in the French study published in this issue, the In the event that the final pathology report demonstrated a feature that did not meet eligibility criteria for the trial, the PBI intraoperative radiation was considered as a boost, and the patient went on to also receive whole-breast external beam radiation, using a dose of 46-50 Gy. A total of 36% of the patients in the trial required further external beam radiation.…”
mentioning
confidence: 99%
“…In the discussion section of that report, mention was made of the original Target A Trial, but long‐term results have not been published. The trial was designed as a noninferiority trial, and failed to show noninferiority 6 …”
mentioning
confidence: 99%